Adverse Outcome Pathways can drive non‐animal approaches for safety assessment. Issue 9 (5th May 2015) - Burden, Natalie; Sewell, Fiona; Andersen, Melvin E.; Boobis, Alan; Chipman, J. Kevin; Cronin, Mark T. D.; Hutchinson, Thomas H.; Kimber, Ian; Whelan, Maurice
Abstract: Adverse Outcome Pathways (AOPs) provide an opportunity to develop new and more accurate safety assessment processes for drugs and other chemicals, and may ultimately play an important role in regulatory decision making. Not only can the development and application of AOPs pave the way for the development of improved evidence‐based approaches for hazard and risk assessment, there is also the promise of a significant impact on animal welfare, with a reduced reliance on animal‐based methods. The establishment of a useable and coherent knowledge framework under which AOPs will be developed and applied has been a first critical step towards realizing this opportunity. This article explores how the development of AOPs under this framework, and their application in practice, could benefit the science and practice of safety assessment, while in parallel stimulating a move away from traditional methods towards an increased acceptance of non‐animal approaches. We discuss here the key areas where current, and future initiatives should be focused to enable the translation of AOPs into routine chemical safety assessment, and lasting 3Rs benefits. © 2015 The Authors. Journal of Applied Toxicology published by John Wiley & Sons Ltd. Abstract : This article explores how the development and application of Adverse Outcome Pathways (AOPs) could benefit the science and practice of chemical safety assessment, with a particular focus on how their use in practice could reduce reliance on traditional animal toxicity tests. This includes discussion of the key areas where current and future initiatives should be focused to enable the translation of AOPs into routine chemical safety assessment, and lasting 3Rs benefits.